Surface Design Options in Polymer- and Lipid-Based siRNA Nanoparticles Using Antibodies - Gabel, Michael; Knauß, Annkathrin; Fischer, Dagmar; Neurath, Markus; Weigmann, Benno (International Journal of Molecular Sciences, 2022)
The mechanism of RNA interference (RNAi) could represent a breakthrough in the therapy of all diseases that arise from a gene defect or require the inhibition of a specific gene expression. In particular, small interfering RNA (siRNA) offers an attractive opportunity to achieve a new milestone in the therapy of human diseases. The limitations of siRNA, such as poor stability, inefficient cell uptake, and undesired immune activation, as well as the inability to specifically reach the target tissue in the body, can be overcome by further developments in the field of nanoparticulate drug delivery. Therefore, types of surface modified siRNA nanoparticles are presented and illustrate how a more efficient and safer distribution of siRNA at the target site is possible by modifying the surface properties of nanoparticles with antibodies. However, the development of such efficient and safe delivery strategies is currently still a major challenge. In consideration of that, this review article aims to demonstrate the function and targeted delivery of siRNA nanoparticles, focusing on the surface modification via antibodies, various lipid- and polymer-components, and the therapeutic effects of these delivery systems.
CRIS-Team Scopus Importer:2022-12-09
Keywords: antibody; gene delivery; lipid nanoparticle; polymer nanoparticle; siRNA; surface-functionalized nanoparticles; targeted drug delivery